Possible role of vitamin D supplementation in coronavirus disease 2019 - Dayal, Devi (International Journal of Scientific Reports, 2020)
Vitamin D deficiency (VDD) is presumed to play a role in several infective and non-infective conditions such as acute respiratory infections, tuberculosis, diabetes, hypertension, stroke etc. Most of the respiratory viral infections occur during winter season when the vitamin D levels in most individuals are generally low. The current pandemic of coronavirus disease 2019 (COVID-19) which began during winter season similar to the previous epidemics due to coronaviruses, has again stirred a debate on the role of VDD in the initiation and spread of the pandemic. The data on vitamin D status in patients with COVID-19 is however lacking. Different vitamin D supplementation strategies have recently been suggested as part of several countermeasures aimed at reducing the impact of COVID-19 pandemic. This brief narrative review discusses the evidence for the link between VDD and COVID-19 and the approaches suggested for vitamin D supplementation.